2018
DOI: 10.1016/j.jtcvs.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of postoperative lung function after major lung resection for lung cancer using volumetric computed tomography

Abstract: Volumetric computed tomography is a reliable and accurate method to predict postoperative lung function in patients undergoing lung resection that provides better accuracy than conventional procedures. Because lung computed tomography is systematically performed in the staging of patients with suspected lung cancer, this volumetric analysis might simultaneously provide the information necessary to evaluate operability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…O/E functional loss ratio Traditionally, pulmonary function loss after lung resection is thought to be in direct proportion to the number of resected segments, leading to the assumption that segmentectomies might preserve more function than lobectomies. However, previous studies have noticed that pulmonary function after lung resection might be inaccurately predicted by the segment counting method due to various factors including the baseline lung function, different intervals between surgery and the postoperative spirometry test (8,21,22), impacts from the surgical incisions (23,24), different compensatory lung expansion after various extent of resections and various lobes resected (25). In this study, we compared the expected pulmonary function loss with the actual loss observed at a fixed interval between spirometry tests after VATS lung resection in functionally fit patients.…”
Section: Discussionmentioning
confidence: 99%
“…O/E functional loss ratio Traditionally, pulmonary function loss after lung resection is thought to be in direct proportion to the number of resected segments, leading to the assumption that segmentectomies might preserve more function than lobectomies. However, previous studies have noticed that pulmonary function after lung resection might be inaccurately predicted by the segment counting method due to various factors including the baseline lung function, different intervals between surgery and the postoperative spirometry test (8,21,22), impacts from the surgical incisions (23,24), different compensatory lung expansion after various extent of resections and various lobes resected (25). In this study, we compared the expected pulmonary function loss with the actual loss observed at a fixed interval between spirometry tests after VATS lung resection in functionally fit patients.…”
Section: Discussionmentioning
confidence: 99%
“…For many years, perfusion scintigraphy has been the gold standard for estimating postoperative lung function. Recently, several trials were conducted using CT volumetry [ 3 - 6 ]. As technology has advanced, CT volumetric analysis has provided better estimations of predicted postoperative lung function than the methods previously mentioned [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several trials were conducted using CT volumetry [ 3 - 6 ]. As technology has advanced, CT volumetric analysis has provided better estimations of predicted postoperative lung function than the methods previously mentioned [ 3 ]. The development of programs that work with CT data has facilitated the construction of 3-dimensional (3D) models, allowing resected lung volume to be calculated from the virtual boundaries of the 3D model [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This consistency might be interpreted as the alveolar consolidation caused by inflammation, which directly affected the normal ventilation/perfusion (V/Q) homeostasis and thus compromised patients' pulmonary function, and this abnormality could be sensitively detected by chest CT. Thus, quantitative analysis of volume and density based on CT is correlated with respiratory function and can accurately reflect patients' clinical course [21].…”
Section: Discussionmentioning
confidence: 99%